2015
DOI: 10.1371/journal.pone.0143640
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Effects of the Fusarium Mycotoxins Deoxynivalenol, 3 Acetyldeoxynivalenol, and Moniliformin and Their Transfer to the Brain

Abstract: BackgroundSecondary metabolites produced by Fusarium fungi frequently contaminate food and feed and have adverse effects on human and animal health. Fusarium mycotoxins exhibit a wide structural and biosynthetic diversity leading to different toxicokinetics and toxicodynamics. Several studies investigated the toxicity of mycotoxins, focusing on very specific targets, like the brain. However, it still remains unclear how fast mycotoxins reach the brain and if they impair the integrity of the blood-brain barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 52 publications
(81 reference statements)
1
42
0
Order By: Relevance
“…Several mechanisms have been proposed to contribute to the reduction in feed intake induced by DON-contaminated feed. Some studies have shown that DON can cross the blood-brain barrier, leading to activation of central structures and affecting glial cell viability and function (Behrens et al 2015;Razafimanjato et al 2011). Other experiments have suggested a DONinduced reduction in plasma insulin-like growth factor acid-labile subunit (IGFALS) (Flannery et al 2013) and an increased pro-inflammatory cytokine expression (Pestka and Amuzie 2008), effects that initiate anorexia and poor growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to contribute to the reduction in feed intake induced by DON-contaminated feed. Some studies have shown that DON can cross the blood-brain barrier, leading to activation of central structures and affecting glial cell viability and function (Behrens et al 2015;Razafimanjato et al 2011). Other experiments have suggested a DONinduced reduction in plasma insulin-like growth factor acid-labile subunit (IGFALS) (Flannery et al 2013) and an increased pro-inflammatory cytokine expression (Pestka and Amuzie 2008), effects that initiate anorexia and poor growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular viability was tested after treatment for 48 h using the CCK-8 assay, like applied for the cell lines but with minor modifications. Based on earlier protocols [ 16 , 22 ] for the cultivation of PBCEC, the cryopreserved PBCEC were thawed at 37°C in a water bath, gently resuspended in culture medium (Medium 199 Earle’s with 100 U/mL penicillin, 100 μg/mL streptomycin, 100 μg/mL gentamycin, 4.1 mM l -glutamine and 10% fetal calf serum) and centrifugated at 220 × g at 20°C for 10 min. After removal of the supernatant, fresh complete medium was added and the cell pellet was resuspended twice and diluted to desired cell density.…”
Section: Methodsmentioning
confidence: 99%
“…Such TEER values are often not attained by other in vitro- cell culture models that are applied for transport studies. This property of the PBCEC is close to the in vivo -situation and ensures the tightness and reliability of a barrier system to study transport characteristics [ 16 , 20 , 22 ]. In order to assess the possibility of ENNs reaching the brain, the transport kinetics of ENN B and B1 were evaluated using this in vitro -cell culture system based on PBCEC mimicking the BBB.…”
Section: Introductionmentioning
confidence: 96%
“…MON did not affect intestinal nor blood capillary integrity in vitro. However, in vitro studies suggest that the molecule can pass the blood brain barrier [ 59 , 106 ]. After single oral gavage, 42% of the administered MON was excreted in the urine of rats within 24 h post administration, and less than 1% was excreted in the feces.…”
Section: Moniliforminmentioning
confidence: 99%